2011
DOI: 10.1161/cir.0b013e3182285a81
|View full text |Cite
|
Sign up to set email alerts
|

Value of Primordial and Primary Prevention for Cardiovascular Disease

Abstract: Abstract-The process of atherosclerosis may begin in youth and continue for decades, leading to both nonfatal and fatal cardiovascular events, including myocardial infarction, stroke, and sudden death. With primordial and primary prevention, cardiovascular disease is largely preventable. Clinical trial evidence has shown convincingly that pharmacological treatment of risk factors can prevent events. The data are less definitive but also highly suggestive that appropriate public policy and lifestyle interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
282
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(289 citation statements)
references
References 184 publications
1
282
1
5
Order By: Relevance
“…To prevent future cardiovascular devastating events, each component of the syndrome must be identified as early as possible. Early diagnosis and treatment for hypertension [29] and dyslipidemia have the potential to reduce teenagers' risk of developing CVD in adulthood [7,30]. Assessment of structure/function measures of the vasculature by simple noninvasive methods can identify early vascular damage in young asymptomatic subjects.…”
Section: Screening For High Blood Pressure In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent future cardiovascular devastating events, each component of the syndrome must be identified as early as possible. Early diagnosis and treatment for hypertension [29] and dyslipidemia have the potential to reduce teenagers' risk of developing CVD in adulthood [7,30]. Assessment of structure/function measures of the vasculature by simple noninvasive methods can identify early vascular damage in young asymptomatic subjects.…”
Section: Screening For High Blood Pressure In Childrenmentioning
confidence: 99%
“…As a consequence, efforts for combating future CVD should be directed to prevent MetS and lifelong exposure to cardiometabolic risk in children. Acknowledging the potential implications for public health, screening for cardiovascular risk factors in children is now recommended by American Academy of Pediatrics (AAP) [6], American Heart Association (AHA) [7], and National Heart, Lung, and Blood Institute [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization studies support a causal role for obesity in abnormal cardiovascular disease risk factors for the development of adult atherosclerosis 19, 20. Identifying children based on adiposity who are at risk for clinically evident cardiovascular disease later in life may be an important strategy for cardiovascular disease prevention 18, 21…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the main risk factors associated with cardiovascular disease are preventable and modifi able by lifestyle changes (1). Evidence has shown that overweight, eating behaviors and physical activity affect most cardiometabolic variables associated with cardiovascular risk factors, such as serum lipids, blood pressure, waist circumference and insulin resistance (2).…”
Section: Introductionmentioning
confidence: 99%